Breast feeding and insulin levels in low birth weight neonates - Jose, Santhosh; K., Mohamad Ismael (International Journal of Contemporary Pediatrics, 2017)
Background: Low birth weight (LBW) is defined by the World Health Organization as a birth weight of an infant of 2,499 g or less, regardless of gestational age. Low birth is caused mainly due to diabetes and cardiovascular diseases in adults This study compared breast feeding with or without supplemental feeding on short term growth patterns and fasting insulin levels in low birth weight neonates. Methods: This study was conducted in Department of Paediatric and it was approved by institutional review board. 100 low birth weight neonates who were less than 2.5 Kg who were born at >38 weeks of gestation, less than 10 days of age, were enrolled in the study. 50 children’s parents provided informed consent (50%) and assured follow-up were included in the study. Children born after 38 weeks of gestation, low birth weight, having no intercurrent illnesses such as acute infections or congenital malfunctions were included in the study. These children were randomly divided into two groups, Group I consisted of 25 were made to receive breast feeding, Group II consisted of 25, received fortified meal along with breast feeding. Results: In the present study, birthweight was 2.00±0.58 in group I, and it was 1.88±0.35 kg in group II; birth length was 43.5±2.5 in group I and it was 43.8±2.8 cm in group II; head circumference was 31.2±1.4 in group I and it was 30.25±8.7 cm in group II; chest circumference was 29.1±2.8 in group I and it was 28.7±5.8 in group II. Haemoglobin levels, glucose fasting levels were lesser in group II compared to group I and insulin levels and IQR levels were more in group II compared to group I. Conclusions: Those low birth weight neonates who had exclusive breast feeding had lesser fasting insulin levels when compared to those who were fed with fortified breast milk.